BENTUK DAN FUNGSI SAWANAN UNTUK IBU HAMIL DAN BAYI BAGI MASYARAKAT DESA NGELUK, KEC. PENAWANGAN : KAJIAN FOLKLOR - Endang Astuti; Harjito (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Beliefs and protective practices for pregnant women and infants in Javanese society constitute a living folkloric system that persists to the present day. This study examines the forms and functions of sawanan for pregnant women and infants in Ngeluk Village, Penawangan District, Grobogan Regency. The research focuses on the use of bengkle and dlingu plants as media of protection against supernatural disturbances. A folkloristic approach was employed using ethnographic methods, including observation, interviews, and the exploration of local belief data. The findings indicate that sawanan functions as a cultural mechanism to avert supernatural threats, strengthen social solidarity, and maintain cosmological balance within Javanese families. The bengkle and dlingu plants are not merely herbal rhizomes but symbols of apotropaic energy believed to protect pregnant women and infants from interference by supernatural beings. This study demonstrates that such beliefs remain enduring because they provide a sense of security and explanations for phenomena that are difficult to comprehend through everyday rationality.